2013
DOI: 10.1021/jm301882a
|View full text |Cite
|
Sign up to set email alerts
|

GC-Targeted C8-Linked Pyrrolobenzodiazepine–Biaryl Conjugates with Femtomolar in Vitro Cytotoxicity and in Vivo Antitumor Activity in Mouse Models

Abstract: DNA binding 4-(1-methyl-1H-pyrrol-3-yl)benzenamine (MPB) building blocks have been developed that span two DNA base pairs with a strong preference for GC-rich DNA. They have been conjugated to a pyrrolo[2,1-c][1,4]benzodiazepine (PBD) molecule to produce C8-linked PBD-MPB hybrids that can stabilize GC-rich DNA by up to 13-fold compared to AT-rich DNA. Some have subpicomolar IC50 values in human tumor cell lines and in primary chronic lymphocytic leukemia cells, while being up to 6 orders less cytotoxic in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 61 publications
1
75
0
Order By: Relevance
“…We have synthesized the amide 3 starting from 2-trichloroacetyl-1-methyl-4-nitropyrrole (1) [12,13] according to Scheme 1, in two steps; the first was performed by acyl nucleophilic substitution of the OPEN ACCESS trichloromethyl leaving group by ethanolamine to afford amide 2 and the second by protecting the hydroxyl group with an acetyl group to furnish ester 3 [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have synthesized the amide 3 starting from 2-trichloroacetyl-1-methyl-4-nitropyrrole (1) [12,13] according to Scheme 1, in two steps; the first was performed by acyl nucleophilic substitution of the OPEN ACCESS trichloromethyl leaving group by ethanolamine to afford amide 2 and the second by protecting the hydroxyl group with an acetyl group to furnish ester 3 [14].…”
Section: Resultsmentioning
confidence: 99%
“…After completion of the reaction (by TLC) the reaction mixture was concentrated and then the residue was dissolved in degassed CH 2 Cl 2 containing Et 3 N. Finally, the reaction mixture was concentrated and the title compound 5 was then purified by silica gel chromatography. The required compound 5 obtained in 70% overall yield from 3 was characterized by 1 H-NMR, 13 C-NMR and mass spectral data.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of a thermallyinduced cleavage assay, they reported that 3 forms cross-links at the 5'-AATTTTCC(G)-3' sequence. During the past six years we have developed molecular dynamics simulation methodologies [11,13,48] that allow us to accurately predict and interpret how both mono-alkylating and DNA cross-linking agents of this type interact in the minor groove of DNA. As the hybrid dimer 3 reported by Lee [47] had a significantly lower DNA cross-linking potency and in vitro cytotoxicity compared to the Hurley (1) and Denny (2) dimers, we decided to use our simulation methodologies to compare the interaction of the three molecules at their proposed DNA recognition sites.…”
Section: Introductionmentioning
confidence: 99%
“…Through the years, many novel cross-linking agents have been designed, synthesized and evaluated [4] , [5] in an attempt to (a) improve on cross-linking efficiency [6], (b) modify the sequence-selectivity of cross-linking [7], (c) change the distribution of inter-versus intrastrand cross-links [8][9][10], and/or (d) target different base pair combinations [11][12][13]. For example, the naturally occurring pyrrolobenzodiazepine (PBD) molecules, derived from Streptomyces species [14][15][16][17][18], are characterized by an N10-C11 imine group that enables formation of a covalent bond to the C2-amino group of a guanine base [19], and these have been successfully incorporated into PBD dimer structures such as DSB-120 [20] and SJG-136 [21] (Figure 1A) that can form sequence-selective G-G cross-links in the DNA minor groove.…”
mentioning
confidence: 99%
“…Synthetic hybrids [5][6][7][8] and dimers [5,[9][10][11] have also shown significant biological activity and members of the dimer class have entered Phase II clinical development as antitumour compounds. PBDs with additional fused rings such as the circumdatin (4) [12], bretazenil (5) [13] and the 1,2,3-triazolo-fused system 6 [14] are attractive as potential antitumour compounds, neurological agents, and protease inhibitors, respectively.…”
Section: Introductionmentioning
confidence: 99%